Assessment of nail findings in children with atopic dermatitis - Uku, S. Arslan; Demir, B.; Cicek, D.; Yuksel, E. Inan (Oxford Univ Press, 2021)
Background Cutaneous findings are well known in atopic dermatitis (AD), but nail changes have not received as much attention. Aim To determine the clinical and disease-related capillaroscopic findings of nail findings in paediatric patients with AD. Methods In total, 100 participants aged 2-16 years were sourced from the dermatology outpatient clinic: 50 of these had been diagnosed with AD according to the Hanifin-Rajka criteria, and the others were 50 healthy controls (HCs) without AD. The AD severity score (SCORing Atopic Dermatitis; SCORAD) was calculated for all patients with AD. A digital epiluminescence device was used for nailfold capillaroscopy. Results The nail findings detected in patients with AD were pitting, punctate leuconychia, trachyonychia, onycholysis and onychomadesis. Pitting was significantly (P < 0.01) more frequent in the patient group (26%) than in the HC group (6%). Similarly, the patient group had significantly higher rates for capillary density decrease (P < 0.01), capillary array irregularity (P < 0.001), capillary dilatation increase (P < 0.001), tortuosity (P = 0.04), ramification increase (P = 0.02), bush-like appearance (P = 0.02) and avascular areas (P < 0.01). Significant correlations were determined between pitting and trachyonychia (P < 0.05, r = 0.21), capillary density decrease (P < 0.05, r = 0.25), avascular areas (P r = 0.29) and SCORAD (P < 0.05, r = 0.35). Conclusion The nailfold capillaroscopic images of children with AD were similar to those of scleroderma spectrum disorder. Thus, we believe it would be beneficial to support detailed clinical examination of patients with a capillaroscopic examination.
Keywords: Systemic-Sclerosis; Capillaroscopy; Skin; Morphology; Diagnosis